Use of botulinum toxin type A (Botox) in the treatment of infantile cerebral palsy - A. L. Kurenkov; O. A. Klochkova; B. I. Bursagova; L. M. Kuzenkova; Kh. M. Karimova; A. M. Mamedyarov; A. R. Artemenko; S. A. Petrova (Нервно-мышечные болезни, 2015)
Botulinum toxin type A (BoNT-A) is used in cerebral palsy (CP) for more than 20 years. Nevertheless, the unified protocol of injections and doses does not exist by now. The correct selection of target muscles for BoNT-A injections is based on the experience of the doctor, detailed analysis of neurological and orthopedic status of the patient, standard scales to evaluate motor potential of the patient. The article represents the detailed review of international clinical trials for multi-level use of BoNT-A in CP and recommendations on doses calculation. Based on our own observations of efficacy and safety of single-used doses of Botox we present the recommended dose ranges for upper and lower limb that led to clinically significant decrease of spasticity with no undesirable weakness. The review of clinical cases presents the doses per targeted muscle and total doses we used, they are advisory in nature.